The crisis of fair value accounting: Making sense of the recent debate - Christian Laux; Christian Leuz (Goethe University Frankfurt, Center for Financial Studies (CFS), 2009)
The recent financial crisis has led to a vigorous debate about the pros and cons of fair-value accounting (FVA). This debate presents a major challenge for FVA going forward and standard setters' push to extend FVA into other areas. In this article, we highlight four important issues as an attempt to make sense of the debate. First, much of the controversy results from confusion about what is new and different about FVA. Second, while there are legitimate concerns about marking to market (or pure FVA) in times of financial crisis, it is less clear that these problems apply to FVA as stipulated by the accounting standards, be it IFRS or U.S. GAAP. Third, historical cost accounting (HCA) is unlikely to be the remedy. There are a number of concerns about HCA as well and these problems could be larger than those with FVA. Fourth, although it is difficult to fault the FVA standards per se, implementation issues are a potential concern, especially with respect to litigation. Finally, we identify several avenues for future research.
urn:nbn:de:hebis:30-65780
Keywords: G14; G15; G30; K22; M41; M42; 330; Mark-to-market; Fair value accounting; Financial institutions; Liquidity; Financial crisis; Banks; Procyclicality; Fair-Value-Bewertung; Bankbilanz; Kritik; Finanzmarktkrise; Welt